Outward FDI and sustainable trade balance path : evidence from portuguese economy, 1996 - 2011 - Fonseca, Miguel (2016)
In the last two decades the internationalisation of the Portuguese economy increased, particularly through outward FDI on the Portuguese-speaking countries. Different studies in economic literature conclude for the existence of a complementary relationship between foreign production and trade in traditional outward investing economies, contributing to the long term sustainable path of the country’s trade balance. In our paper we discuss if this hypothesis holds for a new outward investor like Portugal, with reference to the period 1996-2011. We use a panel data analysis within a framework of gravity models for exports and imports, with a sample composed by EU-15, U.S.A., Brazil, Angola, Spain, Japan and China. Our main conclusion is that the Portuguese outward FDI seems to be negatively related to exports, suggesting a substitution effect, and thus a negative trade balance effect, for the majority of countries in our sample. The exception to this tendency seems to be Spain, confirming and reinforcing a former study for the period 1996-2007. Angola also reveals a positive effect on exports but, in this case, the effect on imports outweighs that on exports, contradicting the results obtained in that same former study. The results we achieved now suggest that the expected positive impact on home country´s trade of the increased internationalisation of the Portuguese economy as an exporter of capital, on the last fifteen years, is not evident and continue to be not predicable with certainty relying on empirical evidence.